Without using a calculator , solve for x in the following equation: lo g 5 x + lo g 7 x = lo g 2 5 x
Oh yeah! You don't need a graphing software as well. ^_^ good luck.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done!!!
Change of base (I've used natural log here, it doesn't really matter)
l n ( 5 ) l n ( x ) + l n ( 7 ) l n ( x ) = l n ( 2 5 ) l n ( x )
Moving everything to one side, we get:
l n ( 5 ) l n ( x ) + l n ( 7 ) l n ( x ) - l n ( 2 5 ) l n ( x ) = 0
Factoring ln(x) out:
ln(x) ( l n ( 5 ) 1 + l n ( 7 ) 1 - l n ( 2 5 1 ) = 0
Since whatever inside the bracket does not equal to 0 (you can further simplify it if you want):
ln(x) = 0
That leads us to:
x = 1
Problem Loading...
Note Loading...
Set Loading...
lo g 5 x + lo g 7 x lo g 5 lo g x + lo g 7 lo g x lo g x ( lo g 5 1 + lo g 7 1 ) ⟹ lo g x x = lo g 2 5 x = lo g 2 5 lo g x = lo g 2 5 lo g x = 0 = 1 Converting to same base Since lo g 5 1 + lo g 7 1 = lo g 2 5 1